An Analysis Of Social Discrimination Forms Of Workplace Inclusion For People With Disabilities: A Literature Study - Murtiasih; Ahsan Romadlon Junaidi; Dimas Arif Dewantoro; Muchamad Irvan (International Inclusion Development and Cooperation, 2023)
Article 67, paragraph 1, of Law Number 2, Year 2022 states that every company is obliged to provide protection in accordance with the type and degree of disability. However, in reality, there are still many companies that accept people with disabilities as workers without providing appropriate services. There is still discrimination, stigma, prejudice, and bad stereotypes about people with disabilities who work. Therefore, researchers want to know the forms of discrimination experienced by workers with disabilities. Researchers used a literature review approach by searching for data related to social inclusion for people with disabilities in the workplace through supporting data sourced from national and international research journals. From the results that have been obtained, researchers found that the form of discrimination that arises in the work environment is that there are still many non-disabled employees who look down on them, such as considering that employees with disabilities are childish, incompetent, dangerous, cannot complete tasks optimally, and have deviant sexual disorders. In addition, employers impose restrictions on working hours for people with disabilities, lack of access to flexible transportation, and assigning tasks that are in a quiet and monotonous place make employees with disabilities uncomfortable, not invited to discuss and left to sit in the chair alone. From several cases that have been obtained by researchers, it can be concluded that social inclusion in the field of employment for people with disabilities is still not fully inclusive. And the laws that have been made by the government still cannot be implemented perfectly.